Inflammation as a Modulator of Host Susceptibility to Pulmonary Influenza, Pneumococcal, and Co-Infections - Aguilera, Elizabeth R.; Lenz, Laurel L. (Frontiers in Immunology, 2020)
Bacterial and viral pathogens are predominant causes of pulmonary infections and complications. Morbidity and mortality from these infections increases in populations that include the elderly, infants, and individuals with genetic disorders such as Down syndrome. Immune senescence, concurrent infections, and other immune alterations occur in these susceptible populations, but the underlying mechanisms that dictate increased susceptibility to lung infections are not fully defined. Here, we review unique features of the lung as a mucosal epithelial tissue and aspects of inflammatory and immune responses in model pulmonary infections and co-infections by influenza virus and Streptococcus pneumoniae. In these models, lung inflammatory responses are a double-edged sword: recruitment of immune effectors is essential to eliminate bacteria and virus-infected cells, but inflammatory cytokines drive changes in the lung conducive to increased pathogen replication. Excessive accumulation of inflammatory cells also hinders lung function, possibly causing death of the host. Some animal studies have found that targeting host modulators of lung inflammatory responses has therapeutic or prophylactic effects in these infection and co-infection models. However, conflicting results from other studies suggest microbiota, sequence of colonization, or other unappreciated aspects of lung biology also play important roles in the outcome of infections. Regardless, a predisposition to excessive or aberrant inflammatory responses occurs in susceptible human populations. Hence, in appropriate contexts, modulation of inflammatory responses may prove effective for reducing the frequency or severity of pulmonary infections. However, there remain limitations in our understanding of how this might best be achieved – particularly in diverse human populations.